Gerak Progresif Gerakan Gay Kontemporer di Yogyakarta - Capriati, Wigke; Permana, Yogi Setya (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2008)
Gay as a social phenomenon has increasingly apparent and attracts many social scientists. Among other area, gay movement in Yogyakarta has demonstrated a vibrant and progressive movement. However, gay movement in Yogyakarta is not growing without challenges. Since it first appearaizce in 1980s, gay movement in Yogyakarta has been evolved substantively in terms of size, approach, and magnitude. Based on close observation and interview with gay activists in Yogyakarta, this paper aims to figure out the nature of gay movement in Yogyakarta and describes their struggle for coexistence among social communities in Yogyakarta.